We Wanna Boogie : The Rockabilly Roots of Sonny Burgess and the Pacers - Schwartz, Marvin, 1948- (Book collections on Project MUSE., 2014)
Marvin Schwartz is a freelance writer who specializes in Arkansas history and culture. He has worked as a journalist, educator, speechwriter, and grant writer and has directed nonprofit organizations. He holds an MFA in poetry from the University of Arkansas.